Korean Confucianism the philosophy and politics of Toegye and Yulgok - Kim, Hyŏng-ch'an, 1963- (CEACOP East Asian comparative ethics, politics and philosophy of law., 2018)
"This book explores Neo-Confucianism and its relationship to politics by examining the life and work of the two iconic figures of the Joseon dynasty Yi Hwang, (1501-1570, Toegye) and Yi I (1536-1584, Yulgok)"--